Irish actuarial data - Honohan, W. A. (Statistical and Social Inquiry Society of Ireland, 1946)
In Eire, we have had three National Life Tables, prepared in connection with the 1926 and 1936 Censuses and the 1941 Register of Population. In each case there are separate tables for males and females and, for 1941, tables (male and female) for Urban Areas. In a similar manner to Great Britain, the Insurance Act, 1936, prescribes the Eire Life Table No. 1 (Males) as the basis to be used in the calculation of free paid-up policies and of surrender values of industrial assurance policies, but no monetary functions have been published, except those given in a short illustrative paper of mine which was published in the Journal of the Institute of Actuaries (Vol. 68, p. 168). To complete the picture, I should mention the unofficial regional life tables presented to this Society by Mr. Colm A. Barry on the 31st October, 1941. I now propose briefly to survey the existing material, and to present certain new statistics and functions.
Read on Friday, 15th December, 1944
Keywords: Actuarial data, Ireland; Life tables; Demographics, Ireland; Life assurance; 314.15